High Fat Diet Induces Kidney Injury via Stimulating Wnt/β-Catenin Signaling - Yu, Ying; Mo, Hongyan; Zhuo, Hui; Yu, Chen; Liu, Youhua (Frontiers in Medicine, 2022)
High fat could cause kidney injury, and the underlying mechanism remains incompletely understood. In this study, we investigated the role of Wnt signaling in this process. Mice were fed with a high-fat diet in vivo, and podocytes were stimulated with palmitate in vitro. In mice fed with high-fat diet, renal function was impaired, which was accompanied by induction of various proinflammatory cytokines and proteinuria. Renal expression of Wnt ligands was also significantly induced, with Wnt1 and Wnt3a being the most pronounced, in high-fat diet mice. Intervention with ICG-001, a small molecule β-catenin inhibitor, improved renal function, inhibited proinflammatory cytokines expression, reduced proteinuria and alleviated podocyte injury. In palmitate-treated podocytes, intracellular lipid deposition was increased and Wnt1 and Wnt3a expression up-regulated, which was accompanied by an increased proinflammatory cytokines expression and podocyte injury. These lesions caused by palmitate were largely alleviated by ICG-001. Furthermore, ICG-001 also abolished the inhibition of phosphorylated AMPK by palmitate in podocytes or a high-fat diet in mice. These studies suggest that Wnt/β-catenin signaling is involved in the pathogenesis of high-fat-induced kidney injury. Targeting this signaling may be a potential therapeutic strategy for alleviating obesity-associated nephropathy.